The risk of fire sales in the tri-party repo market - Brian Begalle; Antoine Martin; James McAndrews; Susan McLaughlin (Federal Reserve Bank of New York, 2013)
This paper studies the risk of fire sales in the tri-party repo market, a large and important market where securities dealers find short-term funding for a substantial portion of their own and their clients' assets. We distinguish between fire sales of assets by a dealer who, facing a run that could lead to default, sells securities to generate liquidity, and fire sales of assets by repo investors after a dealer's default has occurred. While fire sales do cause damage no matter how they arise, the tools available to lessen the harm from the two types of fire sales are different. We find that limited tools are available to mitigate the risk of pre-default fire sales and that no established tools currently exist to mitigate the risk of post-default sales.
Keywords: G01; G18; 330; Fire sale; repo market